2021
DOI: 10.3389/fphar.2021.722730
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Gut Microbiota by Sihocheonggan-Tang Shapes the Immune Responses of Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by complex immune dysregulation and closely related to the gut microbiome. The present study investigated the microbiome-mediated effect of Sihocheonggan-Tang (SHCGT) on AD-like symptoms induced by 2,4-dinitrochlorobenzene (DNCB) in BALB/c mice. DNCB was applied regularly to the ear and dorsal skin of BALB/c mice, and SHCGT was administered orally daily for 2 weeks. The composition of the gut microbiota was analyzed using 16S rRNA sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Hence, we hypothesized that CBD might be involved in regulating the metabolic function of the gut microbiota of epileptic rats. Furthermore, the composition of the gut microbiome and the levels of IL-10, IL-4, and TNF-α were altered in mice after drug intervention, and regulation of SCFAs, microbial metabolites, could affect the expression of IL-6 ( 49 ). Combined with the above analysis, we could speculate that the gut microbiome is involved in the process of CBD alleviating epilepsy, which might be mediated by microbial metabolites regulating inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we hypothesized that CBD might be involved in regulating the metabolic function of the gut microbiota of epileptic rats. Furthermore, the composition of the gut microbiome and the levels of IL-10, IL-4, and TNF-α were altered in mice after drug intervention, and regulation of SCFAs, microbial metabolites, could affect the expression of IL-6 ( 49 ). Combined with the above analysis, we could speculate that the gut microbiome is involved in the process of CBD alleviating epilepsy, which might be mediated by microbial metabolites regulating inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the above findings, mice exhibiting AD-like symptoms induced with transdermal injection of 2,4-dinitrochlorobenzene have lower SCFA levels compared to the healthy littermates. Furthermore, the symptoms of AD in these mice are relieved after treatment, and the SCFA levels are normalized ( Chun et al, 2021 ). These findings underscore the role of the SCFAs as signaling molecules of the gut-skin axis.…”
Section: Relationship Between Scfas and Inflammatory Skin Diseasesmentioning
confidence: 99%
“…These inflammatory keratinocytes involve in the pathophysiology of AD. SFCAs markedly reduce IL-6 and ICAM-1 mRNA levels in human keratinocytes (HaCaT cells) stimulated with TNF-α and INF-γ in vitro ( Chun et al, 2021 ) ( Figure 1 ). In addition, butyrate also inhibits the inflammatory phenotype of cultured human keratinocytes by inducing acetylation of histone H3 lysine 9 (AcH3K9) ( Meijer et al, 2010 ; Traisaeng et al, 2019 ).…”
Section: Relationship Between Scfas and Inflammatory Skin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbes may play a role in the development of AD by regulating the immune system through interactions between the microbes and the host, and in particular, alterations in the gut microbiota affect immune system homeostasis by altering the production of metabolites. Several studies have demonstrated that the development of AD can be prevented by modulating the intestinal flora and metabolites ( Fang et al, 2020 ; Kim et al, 2020 ; Chun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%